The Effect of Price and E-Service Quality on Purchase Decisions: A Study of Grabfood Users - Ahmad Febri Sudrajat; Anik Lestari Andjarwati (Indonesian Journal Publisher, 2026)
This study examines the gaps in previous research regarding the influence of price and e-service quality on purchasing decisions on digital platforms, which have yielded inconsistent results. The novelty of this study lies in re-examining these two variables from the perspective of controllable variables within a digital consumer behavior model, specifically in the context of GrabFood users. This study employs a quantitative approach with a descriptive design and uses multiple linear regression analysis. The results indicate, in part, that price does not have a significant effect on purchase decisions, with a calculated t-value of 1.414 and a significance level of 0.159 (> 0.05). Conversely, e-service quality has a positive and significant effect on purchasing decisions, with a t-value of 7.137 and a significance level of 0.000 (< 0.05). The coefficient of determination (R²) of 0.27 indicates that the research model explains 27.7% of the variation in purchasing decisions, while the remainder is influenced by other variables outside the scope of this study. Theoretically, this study contributes to the development of the literature on digital consumer behavior by demonstrating that, in the context of app-based platforms, price is no longer the primary determinant, while e-service quality has become the dominant factor influencing purchase decisions. These findings underscore the importance of digital service quality in shaping online consumer behavior. The managerial implications suggest that enhancing the competitiveness of digital platforms and fostering sustainable business growth are most effectively achieved by optimizing e-service quality—such as improving system reliability, application usability, transaction security, and service responsiveness. Pricing strategies remain necessary as supporting factors, but they should not be the primary focus in driving consumer purchasing decisions.